2020
DOI: 10.3390/ijms21072648
|View full text |Cite
|
Sign up to set email alerts
|

Multifaceted Role of PRDM Proteins in Human Cancer

Abstract: The PR/SET domain family (PRDM) comprise a family of genes whose protein products share a conserved N-terminal PR [PRDI-BF1 (positive regulatory domain I-binding factor 1) and RIZ1 (retinoblastoma protein-interacting zinc finger gene 1)] homologous domain structurally and functionally similar to the catalytic SET [Su(var)3-9, enhancer-of-zeste and trithorax] domain of histone methyltransferases (HMTs). These genes are involved in epigenetic regulation of gene expression through their intrinsic HMTase activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 289 publications
0
45
0
Order By: Relevance
“…The PRDM variants show an opposite, bivalent "yin-yang" behavior with the PR-plus isoform usually acting as a tumor suppressor, and the PR-minus one functioning as an oncogene (3,7). Of note, the expression level imbalance between the two isoforms in favor of the PR-minus is often observed in many human malignancies being attributed to inactivating mutations or silencing of the complete form and/or increased expression of the PR-minus form (3,(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The PRDM variants show an opposite, bivalent "yin-yang" behavior with the PR-plus isoform usually acting as a tumor suppressor, and the PR-minus one functioning as an oncogene (3,7). Of note, the expression level imbalance between the two isoforms in favor of the PR-minus is often observed in many human malignancies being attributed to inactivating mutations or silencing of the complete form and/or increased expression of the PR-minus form (3,(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…PRDM2a/RIZ1 is also a component of the double-strand break (DSB) repair complex, which is essential for ensuring accurate repair outcome and genomic integrity maintenance (3,8). Basically, RIZ1 cooperates with the macrohistone variant mH2A1.2 to direct the choice between the antagonistic DSB repair mediators, BRCA1 and 53BP1.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that E.C.M. detached cancer cells essentially need to form clusters in order to do a metabolic switch from oxidative phosphorylation to glycolysis to maintain cell proliferation and vitality 17 . Since inhibition of EZH2 was reducing the cell proliferation, we were interested in finding out whether clustering was important for high EZH2 expression in E.C.M.…”
Section: Resultsmentioning
confidence: 99%
“…Our study indicates the potential role of MT1M in biological processes. PRDM1 has been associated with cancer progression, metastasis, and altered expression correlated with poor prognosis in lung cancer [ 37 ]. In ovarian CSCs, PRDM1 might be used as prognostic tool and serve as a new therapeutic target.…”
Section: Discussionmentioning
confidence: 99%